Celestial Messengers Cosmic Rays: The Story of a Scientific Adventure - Bertolotti, Mario. (Astronomers' Universe, 2013)
The book describes from a historical point of view how cosmic rays were discovered. The book describes the research in cosmic rays. The main focus is on how the knowledge was gained, describing the main experiments and the conclusions drawn. Biographical sketches of main researchers are provided. Cosmic rays have an official date of discovery which is linked to the famous balloon flights of the Austrian physicist Hess in 1912. The year 2012 can therefore be considered the centenary of the discovery.